(untitled) (Stamford Journal of Microbiology, 2016)
Lots of reports on the generation of stress by increase in temperature in the bacterial cells especially in Escherichia coli has been observed so far. Current study further emphasized such effect on the cells of Pseudomonas putida (SUBP03). Conventional methods relating growth assessment of bacteria were employed. The optical density of bacterial cells at 600 nm (OD600) in the minimal broth along with the culturable cells were assessed in the form of colony forming units (CFUs) in the minimal agar media at different temperatures (27 °C, 30 °C, 33 °C, 37 °C and 40 °C). Morphological observations were made to further clarify the bacterial physiology and the spot tests were performed to examine the cell viability. Cells of P. putida (SUBP03) were found to grow vigorously at 30 °C, while the growth was found to decline at lower temperature (27 °C) and along with the increase in temperature (at 33 °C, 37 °C and 40 °C). However, the morphological changes were insignificant. Furthermore, cells were noticed to completely lose culturability at 40 °C after 48 hours. Stamford Journal of Microbiology, Vol.5(1) 2015: 9-12